Temperature dependence of the electrical properties of the carbon nanotube/polymer composites (eXPRESS Polymer Letters, 2009)
In this paper, pristine and oxidized multi-walled carbon nanotube (MWCNT)/poly(vinylidene fluoride) (PVDF) composites were prepared and the temperature dependence of some electrical properties of these composites were studied. It is found that the transition temperature (Tt), from positive temperature coefficient (PTC) to negative temperature coefficient (NTC) effect, of the oxidized MWCNT/PVDF composites shifted to a higher temperature. The shift of the Tt of the oxidized MWCNT/PVDF composites can be attributed to the chemical functionalization of the MWCNTs. The dielectric constants of these composites are enhanced remarkably, which can be understood by the interfacial polarization effect. The largest dielectric constant of 3600 is obtained in the composite with about 8 vol% oxidized MWCNTs at 1 kHz. The dielectric constants of these composites increase firstly and then decrease with increasing temperature. However, when the temperature reaches a higher value, the dielectric constants increase again with increasing temperature. The ‘wave’ phenomenon of the temperature dependence of the dielectric constants can be understood by the temperature dependence of the interfacial polarization.